Investigation of Flexible Textile Antennas and AMC Reflectors - M. Mantash; A.-C. Tarot; S. Collardey; K. Mahdjoubi (International Journal of Antennas and Propagation)
In this paper, two different methods for fabric characterization are presented: a single frequency method and a broadband method. Felt and denim fabrics are characterized, and patch antennas are designed using these substrates to test both methods. Prototypes of the antennas on felt and denim are manufactured using conductive textile (called electrotextile) aiming to obtain fully flexible antennas. The prototypes are characterized in anechoic chamber to be compared and obtain conclusions related to the characterization methods. A new dual-band hexagonal AMC reflector combinable with antennas is also proposed to improve their performance and reduce the backward radiation to the human body. A novel broadband CPW-fed monopole antenna is designed to be combined with the AMC. The resulted prototype is characterized and compared with the performance of the CPW-fed antenna alone.